Simulasi Numerik Pengaruh Aspect Ratiodan Sudut Serang Terhadap Performa Turbin Angin Sumbu Vertikal H-Rotor - Kurniawati, Diniar Mungil; Sukanda, Jordan Michael (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2020)
The vertical axis wind turbine is a wind turbine which is rotational axis is perpendicular to the ground surface. The H-rotor vertical axis wind turbine has a number of design parameters that can affect the performance of wind turbines. In this study discussed the effect of aspect ratio (H/D) and angle of attack on the performance of H-rotor wind turbine. Variations on the aspect ratio (H/D) used are 0,64 and 1,56 on the angle of attack is 0o and 5o, the type of airfoil NACA0015. The study method used is a numerical simulation of H-rotor wind turbines with computational fluid dynamics 3 dimension. The wind speed utilized for simulation pupose was 3 m/s. Variations on the Tip speedÂ ratio used are 3; 3,5 and 4 so that produced angular velocity at aspect ratio (H/D) 0,64 are 14,4; 16,8 and 19,2 while at aspect ratio (H/D) 1,56 are 22,5; 26,25 and 30. Results from this study that the H-rotor vertical axis wind turbine with variations on aspect ratio (H/D) 0,64 has variation in the power coefficient (CP) value better than the aspect ratio (H/D) 1,56. That is the power coefficient (CP) value includes 0,388; 0,445 and 0,378 on the angle of attack 0o while 0,390; 0,454 and 0,389 Â on the angle of attack 5o. The variations of angle of attack 5o produces the highest power coefficient (CP), which is 0,454 in the aspect ratio (H/D) 0,64 is 0,417 on the aspect ratio (H/D) 1,56. The H-rotor wind turbine with aspect ratio (H/D) 0,64 and angle of attack 5o on Tip Speed Ratio 3,5 produces the highest power coefficient (CP) value which is 0,454.